Pemanfaatan Limbah Bahan Makanan Untuk Pupuk Kompos di Rutan Kelas IIa Yogyakarta - Farhan Rajwaa Alya Mas’ud; Ali Muhammad (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Bama or food ingredients are raw materials which will then be processed to meet nutritional adequacy rates for prisoners. The large number of inmates who need food needs to be balanced with good processing of leftover food to create a clean and beautiful prison environment. Making organic compost fertilizer is one solution to the large amount of food waste because apart from reducing waste, it can also be used as fertilizer for agricultural plants. EM 4 is a microorganism that accelerates the maturity of organic fertilizer in the composting or decomposition process of organic material.